2015
DOI: 10.1175/jas-d-14-0251.1
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Wake of Madeira: First Aerial Observations and Numerical Simulations

Abstract: The island of Madeira is well known for giving rise to atmospheric wakes. Strong and unsteady atmospheric wakes, resembling a von Kármán vortex street, are frequently observed in satellite images leeward of Madeira, especially during summer months, when conditions favoring the formation of atmospheric wakes occur frequently under the influence of the Azores high. Reported here is the analysis of the first airborne measurements of Madeira’s wake collected during the 2010 Island-induced Wake (I-WA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 29 publications
8
36
0
Order By: Relevance
“…The lee wave train is not visibly influenced by the prominent wake of Madeira (Grubišić et al, 2015) and extends over a distance of 40 km with approximately nine wave crests, hence λ ≈ 4.4 km.…”
Section: Waves Along the Boundary-layer Inversionmentioning
confidence: 99%
“…The lee wave train is not visibly influenced by the prominent wake of Madeira (Grubišić et al, 2015) and extends over a distance of 40 km with approximately nine wave crests, hence λ ≈ 4.4 km.…”
Section: Waves Along the Boundary-layer Inversionmentioning
confidence: 99%
“…A first direct observational experiment in the Madeira wake, based on airborne measurements, was described by Grubišić et al . (2015), revealing the presence of strong lateral shear zones and lee‐side atmospheric eddies. Isolated islands are important sources of ocean vorticity as shown by de Souza et al .…”
Section: Introductionmentioning
confidence: 99%
“…Early remote sensing studies revealed intense vortex shedding downwind of Madeira [ Chopra and Hubert , ]. Subsequent recent atmospheric wake numerical studies and targeted sampling refined the understanding of the complex wake region of Madeira [ Nunalee and Basu , ; Grubišić et al ., ]. Vortex shedding events are most frequent in June–August when the ABL depth is below mountain‐top (<1500) and capped by a strong inversion, thereby favoring resonant interactions with the terrain [ Grubišić et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced lee‐side winds due to terrain blocking are expected to suppress ocean mixing, further contributing to the near‐surface oceanic warming. Indeed, there is a sharp contrast between the calm winds in the lee and the strong winds at the island flank that manifests in the sea state and SST [ Grubišić et al ., ]. The correlation between high SST and low winds was robust during the Madeira measurement campaign, Island‐induced Wake (I‐WAKE).…”
Section: Introductionmentioning
confidence: 99%